SIGNIFICANCE OF JURIDICAL FACTS’ SYSTEM IN CIVIL LAW - Z. R. Rafikova (Russian Journal of Economics and Law)
Objective: to reveal the significance of the juridical facts in civil law for the development of civil law. Methods: dialectical methods, as well as such private-scientific methods as a method of ascent from the concrete to the abstract, analysis, synthesis. Results: changes are proposed to Article 8 of the Civil Code of the Russian Federation. Scientific novelty: currently civil law is being changed considerably, in connection with the need to develop a coherent system of juridical facts in civil law. Provisions of Article 8 of the Civil Code do not allow to build the system of the facts, as the author has studied. In this regard, it is important to first of all clearly identify the grounds for the emergence, changing and termination of civil relations as the list of juridical facts should be exhaustive. Practical value: a clear system of juridical facts in the civil law will allow to solve the cause of legal conflicts, will create an opportunity for effective law enforcement. The findings of the research could be the basis of proposals for civil law optimization.